Analysis of Factors Affecting on Saving Intention in Islamic Bank: The Case in Indonesia - Hariyanto Hariyanto; Bariyyatin Nafi'ah (ITB AAS INDONESIA Surakarta, 2022)
This study aims to investigate the effects of religiosity and service quality on saving intention in Islamic banks towards Muslim communities in East Java Indonesia. In addition, this study also wants to find out whether there is an influence of gender, educational background, Islamic education, and geography on the intention to save in Islamic banks. This study uses a positive approach and structural equation modeling-partial least square (SEM-PLS) analysis technique. The sampling method used in this study is convenience sampling, with a total of 100 respondents. The results reveal that religiosity does not affect the saving intention of Muslim communities, while the service quality has a significant impact on the saving intention of the Muslim communities in East Java Indonesia. This result indicates that the better the service quality of Islamic banks, the more people's saving intentions will increase. Educational background and Islamic education affect the intention to save in Islamic banks, while gender and geography have no effect. The practical implication is the Islamic banks may focus on improving service quality, the financial capability of the bank, customer attraction through employee behavior, focusing on the reputation of the bank, and offering variant services.